A New Multi-Scale Structure Finding Algorithm to Identify Cosmological Structure - Snedden, Ali; Phillips, Lara Arielle; Mathews, Grant J; Coughlin, Jared; Suh, In-Saeng; Bhattacharya, Aparna (arXiv.org, 2014)
We introduce a new self-consistent structure finding algorithm that parses large scale cosmological structure into clusters, filaments and voids. This structure finding algorithm probes the cosmological structure at multiple scales and clas- sifies the appropriate regions with the most probable structure type and size. We show that it reproduces key observational results, including the baryon fraction of ICM, and average temperatures and densities for the different structures.